Neurological masks of the onset of insulin-requiring diabetes in a comorbid patient in the practice of a general practitioner - Marina V. Lebedeva; Vladimir D. Beketov (LLC "MEDIAFORMAT", 2023)
A clinical observation of the onset of pancreatogenic diabetes mellitus with neurological manifestations is presented. Difficulties in glycemic control, the importance of self-monitoring of glycemic indicators by the patient are shown. Pathological substantiation of the high risk of hypoglycemic conditions in patients with pankeatogenic diabetes mellitus is given.